TYFOID FEVER - Inawati, Inawati (Universitas Wijaya Kusuma Surabaya, 2009)
Typhoid fever is a bacterial infectious disease caused by Salmonella typhi. The disease is transmitted through food or water contaminated by feces or urine of people who terinfeksi.Gejala clinical, among others, heat, and complaints of the gastrointestinal tract. Diagnosis based on a diagnose and blood. These diseases include infectious diseases that require antibiotics for treatment. Complications include the complications that can cause intestinal and extra intestinal. At this time have found a vaccine that can prevent this disease typhoid fever.